Glutamate metabolism in plant disease and defense: friend or foe? - Seifi, Hamed Soren; Van Bockhaven, Jonas; Angenon, Geert; Höfte, Monica (Molecular plant-microbe interactions, 2013)
Plant glutamate metabolism (GM) plays a pivotal role in amino acid metabolism and orchestrates crucial metabolic functions, with key roles in plant defense against pathogens. These functions concern three major areas: nitrogen transportation via the glutamine synthetase and glutamine-oxoglutarate aminotransferase cycle, cellular redox regulation, and tricarboxylic acid cycle-dependent energy reprogramming. During interactions with pathogens, the host GM is markedly altered, leading to either a metabolic state, termed "endurance", in which cell viability is maintained, or to an opposite metabolic state, termed "evasion", in which the process of cell death is facilitated. It seems that endurance-natured modulations result in resistance to necrotrophic pathogens and susceptibility to biotrophs, whereas evasion-related reconfigurations lead to resistance to biotrophic pathogens but stimulate the infection by necrotrophs. Pathogens, however, have evolved strategies such as toxin secretion, hemibiotrophy, and selective amino acid utilization to exploit the plant GM to their own benefit. Collectively, alterations in the host GM in response to different pathogenic scenarios appear to function in two opposing ways, either backing the ongoing defense strategy to ultimately shape an efficient resistance response or being exploited by the pathogen to promote and facilitate infection.